A pilot study of school-based Filial Therapy (SBFT) with a group of Australian children attending rural primary schools: the impact on academic engagement, school attendance and behaviour. Issue 3 (2nd July 2020) - Cooper, Jane; Brown, Ted; Yu, Mong-lin
ABSTRACT: School-based Filial Therapy (SBFT), a mental health intervention for primary school children living and remote locations. The SBFT pilot was implemented in three rural primary schools in remote and regional New South Wales, Australia, using a pretest-posttest control group design to investigate the impact of 10-sessions of Filial Therapy with a paraprofessional. Target issues were frequency and severity of school behaviour incidents, attendance, academic effort and performance. Participants were 37 children in the experimental group and 22 children in a control group. An independent samples t-test was conducted with bootstrapping. Statistically significant differences were found between the experimental and control groups in the areas of executive managed behaviour ( M  = 3.286, SD  = 3.161; t (48) = −3.5, p  = .045, two-tailed, BCa 95% CI [−8.529, .642]), student attendance ( M  = 92.989, SD  = 6.992; t (26.6) = 3, p  = .006, two-tailed, BCa 95% CI [6.839, 22.702]) and academic effort and performance outcomes in science ( M  = 2.737, SD  = .872; t (36) = −2, p  = .053, two-tailed, BCa 95% CI [−1.382, .013]); ( M  = 2.053, SD  = .780; t (37) = −2.7, p  = .010, two-tailed, BCa 95% CI [-.845, .038]).